Agro-Tourism Development in Cambodia: A Literature Review - Thol Thea; Serey Mardy (International Journal of Sustainable Applied Sciences, 2023)
Agro-tourism, sometimes referred to as eco-tourism or rural tourism, has gained international acceptance as one of the primary methods for establishing rural sustainability. In this definition, agro-tourism refers to the fusion of agricultural, ecological, and cultural products for a variety of purposes, such as social, educational, recreational, health, and environmental. The agriculture industry is the main driver of the Cambodian economy, and in order to sustain the livelihoods and economics of the people living there, a number of tourism-related companies must expand. Finding the most crucial development methods for Cambodia's agro-tourism sector is the primary objective of this review. Aspects of political stability, the development of rural community infrastructure, strategy plans, tourist product stability, marketing components, information system components, encouraging local tourism, investment appeal, and financial support are among the main essential considerations. Strategies are essential to expeditiously enhancing the agro-tourist activities delineated in government policies, including those pertaining to the agricultural sector, agricultural communities, and nature, culture, and society-related tourism. The review has revealed that a wide range of factors could greatly aid in the adoption of agro-tourism development plans and methodologies throughout Cambodia's diverse ecological zones.